Research on Management Issues and Mechanism Innovation of Ship Registration Port during Ship Operation Stage - Jiang, Xiaoyun (Journal of Theory and Practice of Social Science, 2023)
Safety production is a matter of people's well-being and overall economic and social development. Since the 18th Party Congress, General Secretary Xi Jinping has attached great importance to the work of production safety, repeatedly emphasizing the need to improve the mechanism of risk prevention and resolution, insisting on preventing and resolving major safety risks at source, and strengthening the governance of production safety in key areas such as transportation to curb the occurrence of serious accidents. Strengthening the management of a ship's port registry in accordance with the law can enhance the essential safety level of ships, which is an important element to accelerate the modernization of China's maritime governance system and governance capacity. The research on the key issues and mechanism innovation of the management of ship's port of registry of operating ships is an important part to realize the safety management of the whole chain of ships based on the whole life cycle concept. Starting from the operation stage of ships, this paper proposes to build and improve the intelligent management platform of the port of registry, build the management gate-keeping system of non-system shipping companies, and build the comprehensive quality management system of registered ships, to explore the establishment of credit-based ship It will explore the establishment of credit-based supervision mechanism for ships at the port of registration, improve the management level of ships at the port of registration from the source, and help build a new pattern of water safety governance.